Grudging Acts. (June 2023) - Bottero, Wendy
This article argues for a greater focus on how, and why, social life is often engaged in through grudging acts. Grudging acts are those activities in which we really would rather not participate but which we perform nonetheless. Such acts play a significant role in how many social practices are routinely sustained, but also reworked or undermined. Yet grudgingness is underexplored in social analysis, and its significance for social arrangements is insufficiently examined. This neglect occurs because foregrounding grudging acts requires a focus on key aspects of social life that often slip from view in analysis, and is an omission associated with a number of significant explanatory difficulties.